2011
DOI: 10.1111/j.1460-9592.2011.03603.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative adverse respiratory events in preschool patients with inhaled foreign bodies: an analysis of 505 cases

Abstract: Preoperative respiratory impairment may develop the patients with FBs into postoperative adverse respiratory events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
0
19
1
3
Order By: Relevance
“…[2] In another Asian study, 5.3% of 469 patients, in whom bronchoscopy was unsuccessful, were transferred to an adjacent chest hospital for thoracotomy. [31] In contrast to these studies, Kiyan et al reported no requirement of thoracotomy or tracheotomy and no mortality in their study. [16] Although children in the late diagnosis group, in our study, had a longer duration of hospital stay, the difference was comparable statistically among the groups.…”
Section: Discussionmentioning
confidence: 94%
“…[2] In another Asian study, 5.3% of 469 patients, in whom bronchoscopy was unsuccessful, were transferred to an adjacent chest hospital for thoracotomy. [31] In contrast to these studies, Kiyan et al reported no requirement of thoracotomy or tracheotomy and no mortality in their study. [16] Although children in the late diagnosis group, in our study, had a longer duration of hospital stay, the difference was comparable statistically among the groups.…”
Section: Discussionmentioning
confidence: 94%
“…Some anesthesiologists would prefer control ventilation for this procedure because of its rapid control of the airway and promise of no movement during the FB removal. Disadvantages of controlled ventilation include driving the FB further peripherally (19), barotrauma (6), uncertainty of the anesthesia depth, and worsening ventilation/perfusion (V/Q) ratio, especially in patients with respiratory compromise. Advantages of spontaneous ventilation include better V/Q matching, more effective alveolar ventilation, and no barotrauma.…”
Section: Discussionmentioning
confidence: 99%
“…However, Zhang et al. (6) reported that the rate of occurrence of a pneumothorax is 2.31% in children with preoperative respiratory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…In vielen Kliniken fehlt jedoch die entsprechende Erfahrung im Umgang mit dieser Beatmungsform und es bestehen Sorgen hinsichtlich Dislokation des Fremdkörpers durch den hohen Beatmungsdruck und Sorge vor einem Barotrauma bzw. einem Pneumothorax [18,20].…”
Section: Narkoseführung -Beatmungunclassified